2018
DOI: 10.1021/acs.energyfuels.8b01237
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Experiments on Anthracite Combustion and NOx Emissions with Respect to Swirling Secondary Air for a 300 MWe Deep-Air-Staged Down-Fired Utility Boiler

Abstract: A new deep-air-staging and low-NO x technology has been introduced to a 300 MWe anthracite- and down-fired boiler with swirl burners. Industrial experiments were performed at different outer secondary air vane angles (defined as β) (i.e., 20°, 30°, 40°, and 50°) to evaluate the environmental and economic performance for the retrofitted boiler. Furthermore, combining with the previous investigations on the inner secondary air vane angle (defined as α), the influence degrees of β and α on anthracite combustion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Our tests showed that substituting PSI for PC has a significant positive impact on NO x and SO 2 emissions: the emission of NO x was reduced from approximately 500 to 20 mg/MJ fuel , while the emission of SO 2 was reduced from 230 to 1–7 mg/MJ fuel , depending upon the type of PSI. The NO x emissions for PSI are also significantly lower compared to reported values from industrial PC boilers , (see Table ). Furthermore, the observed NO x emission from PC combustion is similar compared industrial emission, verifying that the EFR and the experimental conditions used in this work are relevant.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Our tests showed that substituting PSI for PC has a significant positive impact on NO x and SO 2 emissions: the emission of NO x was reduced from approximately 500 to 20 mg/MJ fuel , while the emission of SO 2 was reduced from 230 to 1–7 mg/MJ fuel , depending upon the type of PSI. The NO x emissions for PSI are also significantly lower compared to reported values from industrial PC boilers , (see Table ). Furthermore, the observed NO x emission from PC combustion is similar compared industrial emission, verifying that the EFR and the experimental conditions used in this work are relevant.…”
Section: Resultsmentioning
confidence: 60%
“…The rest of the micrometer-sized particles consisted mostly of magnetite (Fe 3 O 4 ). The morphology of the PSI particles changed significantly during combustion: from an irregular shape to a nearly spherical or slightly ellipsoidal shape a The table compares literature data regarding NO emissions from seven industrial PC boilers 39,40 to the data obtained in this study. Some information regarding the boiler, burner arrangement, NO xcontrolling technology, and fuel is also given in the table.…”
Section: Resultsmentioning
confidence: 92%
“…Obviously, the fuel-lean coal/air flow utilizes the reductive exhaust gas to feed the fine pulverized-coal (with high specific surface area and strong reducibility) directly into the high-temperature coal/air flame in the lower part of the lower furnace, acting as dual low-NO x combustion roles of flue gas recirculation and char reburning. In comparison to the conventional wall- or arch-arrangement pattern mainly for fuel combustion (such as the B&W , and MIMSCT furnaces), here the fuel-lean coal/gas flow, acting as dual low-NO x combustion roles of flue gas recirculation and char reburning, is technically located on the newly added lower furnace arch, thereby expanding the reaction space for flue gas recirculation and char reburning. This form can achieve a low-NO x combustion performance as much as possible and meanwhile increase the flame fullness.…”
Section: Methodsmentioning
confidence: 99%
“…Yang et al trialed a proposed hot-air packing technology on a bench-scale W-shaped flame furnace for a low-NO x and high-burnout performance. Through the application of a combined high-efficient and low-NO x technology in both FW and B&W W-shaped flame furnaces, Li’s group gained NO x emissions of 697–1057 mg/m 3 at 6% O 2 and carbon in fly ash of 7.54–11.4%. By positioning fuel-lean nozzles in the near-wall side, redirecting staged air, and introducing the separated OFA to regulate a novel combustion system for a 600 MW e FW W-shaped flame furnace, Ma et al , found that NO x emissions reduced by 42–50% to achieve levels of about 760 mg/m 3 at 6% O 2 , accompanied by a certain increase in the burnout loss.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past three decades, particularly in China, W-shaped flame furnaces have been widely used and continuously developed with changes in the combustion systems and operating conditions to satisfy pollutant emission standards. A 600-MW cascade-arch-firing, W-shaped flame furnace with an advanced fuel and air injecting system for low NOx emissions and unburnt carbon was suggested by Wu et al to solve problems in NOx emissions and high amounts of unburnt carbon . This novel combustion system, employed in a down-fired furnace, was termed a cascade-arch-firing low-NOx and high-burnout configuration (CLHC) and contained several low-NOx combustion technologies, including deep air staging bias combustion and fuel reburning technologies.…”
Section: Cfd Modeling Of Hele Coal Combustionmentioning
confidence: 99%